Hospitality Investment Environment in Russia - DEDUSENKO, Elena Aleksandrovna (Journal of Environmental Management and Tourism, 2017)
This paper focuses on current trends of the hospitality investment environment in Russia and discusses the main factors of macro environment that determine tendencies of the hospitality market in the country. Also the article analyses the issues of business cyclicality in the Russian economy and capital flows into the tourism sector. Hospitality companies as part of various markets such as market of services and tourism market, as well as the property market are a challenging object for investment decisions. Nevertheless, a comprehensive approach to the long-term investment decision making considering both the prospects and the risks will enable potential investors not to miss perspective opportunities of the hospitality business in the countries which demonstrate the gap between supply and demand is favorable for investment.